Association Between Race and Opioid-Induced Respiratory Depression: An International Post Hoc Analysis of the Prediction of Opioid-induced Respiratory Depression In Patients Monitored by Capnography Trial. (29th March 2022) - Sim, Ming Ann; Seet, Edwin; Khanna, Ashish K.; Weingarten, Toby N.; Liew, Lydia; Law, Lawrence Siu-Chun; Liu, Katherine E.; Di Piazza, Fabio; Ti, Lian Kah; ,
Abstract : BACKGROUND: Opioid-induced respiratory depression (OIRD) is common on the medical and surgical wards and is associated with increased morbidity and health care costs. While previous studies have investigated risk factors for OIRD, the role of race remains unclear. We aim to investigate the association between race and OIRD occurrence on the medical/surgical ward. METHODS: This is a post hoc analysis of the PRediction of Opioid-induced respiratory Depression In patients monitored by capnoGraphY (PRODIGY) trial; a prospective multinational observational blinded study of 1335 general ward patients who received parenteral opioids and underwent blinded capnography and oximetry monitoring to identify OIRD episodes. For this study, demographic and perioperative data, including race and comorbidities, were analyzed and assessed for potential associations with OIRD. Univariable χ 2 and Mann-Whitney U tests were used. Stepwise selection of all baseline and demographic characteristics was used in the multivariable logistic regression analysis. RESULTS: A total of 1253 patients had sufficient racial data (317 Asian, 158 Black, 736 White, and 42 other races) for inclusion. The incidence of OIRD was 60% in Asians (N = 190/317), 25% in Blacks (N = 40/158), 43% in Whites (N = 316/736), and 45% (N = 19/42) in other races. Baseline characteristics varied significantly: Asians were older, more opioid naïve, and had higher opioid requirements, while Blacks had higher incidences of heart failure, obesity, and smoking. Stepwise multivariable logistic regression revealed that Asians had increased risk of OIRD compared to Blacks (odds ratio [OR], 2.49; 95% confidence interval [CI], 1.54–4.04; P = .0002) and Whites (OR, 1.38; 95% CI, 1.01–1.87; P = .0432). Whites had a higher risk of OIRD compared to Blacks (OR, 1.81; 95% CI, 1.18–2.78; P = .0067). The model's area under the curve was 0.760 (95% CI, 0.733–0.787), with a Hosmer-Lemeshow goodness-of-fit test P value of .23. CONCLUSIONS: This post hoc analysis of PRODIGY found a novel association between Asian race and increased OIRD incidence. Further study is required to elucidate its underlying mechanisms and develop targeted care pathways to reduce OIRD in susceptible populations.